Building Brand Value Through Consumer Trust in Digital Strategies: Evidence from Indonesia's Beauty Industry - Endarwati, Esti Tri (Ilomata International Journal of Management, 2025)
The aim of this study is to investigate the influence of affiliation, live streaming, viral video content, and social interaction on brand value creation in the beauty product industry in Indonesia with consumer trust as a mediating variable. A quantitative method was employed, and data were collected through 350 samples and analyzed using Structural Equation Modeling (SEM) based on SmartPLS software. The result indicates that all digital marketing channels contribute to building consumer trust, then pushing brand value. Among these channels, interactive community engagement exerts the most profound influence, highlighting the active participation and interaction in digital marketing for beauty products in Indonesia. The study provides practical recommendations for beauty firms to improve their digital marketing via trust-building and brand equity development.